2005
DOI: 10.1021/bi051145r
|View full text |Cite
|
Sign up to set email alerts
|

Sequence-Dependent Peptide Binding Orientation by the Molecular Chaperone DnaK

Abstract: Hsp70-class molecular chaperones interact with diverse polypeptide substrates, but there is limited information on the structures of different Hsp70-peptide complexes. We have used a site-directed fluorescence labeling and quenching strategy to investigate the orientation of different peptides bound to DnaK from Escherichia coli. DnaK was selectively labeled on opposite sides of the substrate-binding domain (SBD) with the fluorescent probe bimane, and the ability of peptides containing N- or C-terminal tryptop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 27 publications
3
22
0
Order By: Relevance
“…The finding that the preferred orientation for peptides binding to HscA is sequence-dependent agrees with our previous studies on DnaK (39). In that work, peptides containing proline in the central positions were found to bind in the opposite direction of peptides containing leucine residues, and modeling studies suggested that geometrical constraints of proline residues restrict the peptide conformation to one that favors the reverse-binding orientation (39).…”
Section: Sequence Determinants For Iscu Peptide Binding To Hscasupporting
confidence: 91%
See 2 more Smart Citations
“…The finding that the preferred orientation for peptides binding to HscA is sequence-dependent agrees with our previous studies on DnaK (39). In that work, peptides containing proline in the central positions were found to bind in the opposite direction of peptides containing leucine residues, and modeling studies suggested that geometrical constraints of proline residues restrict the peptide conformation to one that favors the reverse-binding orientation (39).…”
Section: Sequence Determinants For Iscu Peptide Binding To Hscasupporting
confidence: 91%
“…This indicates that the NR peptides bind to HscA in the forward direction. This binding orientation is opposite that observed for the HscA-ELPPVKI peptide complexes (Figure 3; 30, 31) but is the same as observed for the NR peptide binding in the DnaK(SBD)-NRLLLTG crystal structure (27) and full-length DnaK in solution (39). The finding that the preferred orientation for peptides binding to HscA is sequence-dependent agrees with our previous studies on DnaK (39).…”
Section: Sequence Determinants For Iscu Peptide Binding To Hscasupporting
confidence: 87%
See 1 more Smart Citation
“…27,28 However, the ability of DnaK to bind peptides in both directions has been suggested previously following spectroscopic studies. 29 Both binding modes of the Api88 fragment appear to be stabilized by crystal packing interactions. Substitution of glutamine in position 10 by arginine neither weakened nor strengthened the DnaK binding, which also agrees with the MIC values for E. coli.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The MIC values of these Api137 analogs indicated that the N-terminal sequence tolerated substitutions without major effects on the antibacterial activity (Fig. 4A), although apidaecins and Api88 are presumed to inhibit DnaK by binding of residues 3 to 11 to the substrate binding domain of DnaK (19,35,36). Substitutions of C-terminal residues (Pro-11 to Leu-18) significantly reduced the antibacterial activity in most cases.…”
Section: Fig 1 Degradation Of Api88 In 25% Aqueous Mouse Serum (Top) mentioning
confidence: 98%